Retorika dalam Wacana Pemberitaan Isu Perang Dunia III pada Media Berita CNN Indonesia - Sindi Septa Pratiwi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Communication is a fundamental human need, and language serves as the primary medium for conveying information, including through mass media. In news reporting. language functions not only to deliver facts but also to construct reality through various rhetorical strategies. This study aims to describe the use of Aristotle's rhetorical elements ethos, pathos, and logos in CNN Indonesia's online news discourse concerning the issue of World War III. Employing a descriptive qualitative method, this research analyzed news texts published by CNN Indonesia related to the discourse of World War III. The findings indicate that Aristotle's rhetoric is reflected through the integrated use of ethos, pathos, and logos. Ethos is constructed through the use of credible sources and authoritative institutions that enhance the legitimacy of information. Pathos is manifested in emotive and descriptive language that evokes readers emotions and provides vivid depictions of conflicts and their impacts. Meanwhile, logos is demonstrated through the presentation of factual data and logical cause-and-effect arguments that enable readers to understand the issue rationally and systematically. These findings show that CNN Indonesia strategically utilizes the three rhetorical elements to strengthen credibility, emotional appeal, and logical reasoning in reporting the issue of World War III.
Finalisasi 9 Juli 2026_Yudi
Keywords: Keywords: Aristotle's rhetoric; ethos; logos; pathos; news discourse; CNN Indonesia and World War III